Pengaruh Model Pembelajaran Kooperatif Terhadap Kemampuan Pemecahan Masalah dan Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMP Negeri Kabupaten Enrekang - Nurdin R.; Fadhillah A.P. Likur; Baharuddin (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This study aims to determine the effect of: (1) a description of the problem-solving abilities of class VIII students who are taught using the cooperative learning model type two stay two stray or numbered heads together on the Pythagorean theorem and circle material, (2) description of the mathematical communication skills of class VIII students who are taught using the cooperative learning model type two stay two stray or numbered heads together on the Pythagorean theorem and circle material, (3) the difference in mathematical problem solving abilities of class VIII students who are taught using a two stay two stray cooperative learning model and those taught using a numbered heads together type cooperative model on the Teorema Phytagoras and Circle material, (4) differences mathematical communication skills of class VIII students who are taught using the cooperative learning model type two stay two stray with those taught using the cooperative model type numbered heads together on the Teorema Phytagoras and Circle material. This research is an experimental study with a quasi-experimental by factorial 2x2 design. The population in this study were all grade VIII students of the Enrekang Regency Junior High School with accreditation A consisting of 18 schools and the sample in this study was class VIII B SMP N 1 Baraka who was taught with the TSTS type cooperative learning model totaling 30 students and class VIII A SMP N 2 Anggeraja taught with the NHT type cooperative learning model totaling 30 students in the even semester of the 2019 school year. /2020, the determination of the sample is carried out using the cluster random sampling technique. The instruments in this study were (1) a test of problem-solving skills, (2) a test of mathematical communication skills, and (3) an observation sheet on the implementation of learning. The data analysis techniques used were descriptive analysis and inferential analysis using manova. The results of the study indicate that: (1) there is no significant difference in the mathematical problem solving abilities of students who follow the two stay two stray type of cooperative learning model and those who follow the numbered heads together type of cooperative learning model both on the Teorema Phytagoras material and on the Circle material; (2) there is no significant difference in the mathematical communication ability of students who follow the two stay two stray type of cooperative learning model and those who follow the numbered heads together type of cooperative learning model both on the Teorema Phytagoras material and on the Circle material.